THE METAMORPHIC ROCK-HOSTED GOLD MINERALIZATION AT BOMBANA, SOUTHEAST SULAWESI: A NEW EXPLORATION TARGET IN INDONESIA - Arifudin Idrus; Fadlin Fadlin; Sukmandaru Prihatmoko; I Wayan Warmada; Irzal Nur; Franz Michael Meyer (Pusat Survei Geologi, 2012)
Placer gold has been discovered in Bombana, SE-Sulawesi, Indonesia. The placer gold is not associated with volcanic rock-related gold deposits. This paper discusses the primary gold mineralization as the source of the placer gold. The placer gold is possibly derived from gold-bearing quartz veins hosted by Pompangeo Metamorphic Complex (PMC). Pyrite, chalcopyrite, cinnabar, stibnite and tripuhyite are present. Sheared, segmented vein varies in thickness from 2 cm to 2 m. The veins contain erratic gold in various grades from below detection limit (0.005 g/t) to 134 g/t. At least three generations of veins are identified. The first is parallel to the foliations, the second crosscuts the first generation of veins/foliations, and the third is of laminated deformed quartz+calcite veins at the late stage. The first veins are mostly massive to crystalline, occasionally brecciated and sigmoidal, whereas the second veins are narrower than the first and relatively brecciated. Gold grades in the second and third veins are relatively higher than that in first veins. Fluid inclusion study of quartz veins indicates abundant H2O-NaCl and a small amount of H2O-NaCl-CO2 inclusions. Temperature of homogenization (Th) and salinity of the first vein vary from 184.7 to 245.3 ºC and 5.26 to 9.08 wt.% NaCl eq., respectively. The second generation vein was originated at Th of 132.1-283.4 ºC and salinity of 3.55-5.86 wt.%NaCl eq., whereas the third generation vein formed at lowest Th varying from 114 to 176ºC and less saline fluid at salinity range between 0.35 and 4.03 wt.% NaCl eq. Gold is mainly identified in the form of 'free gold' among silicate minerals. Mineralogically, gold is closely related to cinnabar, stibnite, tripuhyite and possibly minor arsenopyrite. Metamorphogenic gold deposits would be the new target of gold exploration in Indonesia.Keyword: Gold mineralization, orogenic-type, Bombana, Southeast Sulawesi, Indonesia